Industrial policy and manufacturing performance in Nigeria - Egbon, P. C.; National Centre for Economic Management and Administration (Nigeria) (Ibadan, Nigeria : National Centre for Economic Management and Administration, 1995)
This text reveals the relationship between Nigerian industrial policy and the performance of the manufacturing sector.
NCEMA Monograph Series No.7
Includes bibliographical references (p. 84-88).
osa; 24/07/17
Loans
Keywords: Industrial policy; Manufacturing industries